Frailty in elderly diabetes patients - Yanase, Toshihiko; Yanagita, Ikumi; Muta, Kazuo; Nawata, Hajime (ENDOCRINE JOURNAL, 2018)
Frailty is a state of vulnerability and a consequence of cumulative decline in multiple physiological systems over a lifespan. The occurrence of frailty depends on deterioration in muscle and nerve function, declining cardiopulmonary reserve and loss of executive function. Diabetes mellitus (DM) often causes functional impairment in each of the above systems, thus leading to a loss of whole body homeostasis and deterioration in physical function. Inability of self-management in DM patients may also have considerable impact on the development of sarcopenia/frailty. Thus, there may be positive feedback between the progression of diabetic complications and frailty/sarcopenia. While various factors are involved in this process, insulin resistance or insulin depletion may be an important factor in the progression of frailty in diabetes patients since insulin is well known to be an anabolic hormone in muscle. Interestingly, in our study targeting elderly DM patients, low HbA1c was a significant and independent risk factor for frailty, as assessed using a broad sense frailty scale, the Clinical Frailty Scale (CSF), suggesting that reverse metabolism due to malnutrition in elderly type 2 DM patients might be involved. Therefore, an intervention that includes proper nutrition and exercise training may be essential for the prevention of frailty. The pathogenesis of frailty in DM patients is extensively discussed in this review.